Gender bias in the field of economics: an analysis of South African academia - Hitchcock, Siobhan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
In recent years there has been a growing focus internationally on the low participation of females in Economics, both in academia and business. While female enrolment in higher education, including other maths-based subjects, has grown substantially, this has not been the case for Economics. Economics, particularly as one progresses through postgraduate studies to doctoral degrees now stands out as an outlier. A number of reasons have been advanced for this, including the nature of the subject, the type of people it attracts and the lack of female role models. Male and female enrolments in South African HEIs have grown between 2007 and 2017, but females have grown at a faster rate, thus increasing the female share of total enrolments to 59%. Female students are more successful and so make up an even greater proportion of South African graduates. Female enrolments and graduates are also higher than in the US. As in the US there is a significant drop off in female representation when progressing from undergraduate to postgraduate studies in South Africa. When looking at Economics in South Africa in comparison to the broad CESM categories, female enrolment in Economics Bachelor degrees is significantly lower than in Business and Humanities, but on a par with STEM subjects. At the Doctoral level, there are sharp drop offs in female enrolments for all categories. Business and Economics are the laggards at the Doctoral level, below STEM and Humanities. Furthermore, females make up a minority of academic staff in South African HEIs, with males dominating in especially the higher academic ranks. As one moves up the academic ladder, the female share decreases. This research analyses gender compositions of staff and students at South African HEIs. National data are obtained from government publications and data relating to four specific South African universities was obtained directly from the universities. Questionnaires were sent to a sample of academic staff and students who are in the field of economics to identify whether there is a role model effect for economics students and whether female academics experience the same forms of biases, discrimination, or treatment as that identified in international studies. It was concluded that while there are drop offs in the overall female representation of students at the Masters and Doctoral levels in South Africa, this share is gradually increasing. Additionally, Economics seems to perform better than what is depicted in the US, and in comparison to some STEM subjects in South Africa. Furthermore, the environment within the field of academic economics for both female students and staff seems to be more positive than what the international literature depicts for the US. But there are nonetheless different levels of satisfaction between male and female academic economists. While the student surveys revealed that female Economics students do not attach great importance to female role models, there is some evidence of correlation between the percentage of female professors and the percentage of female PhD students across a range of STEM subjects in South Africa.
Keywords: Sexism -- South Africa; Sexism in higher education -- South Africa; Economics-- Study and teaching (Higher) -- South Africa; Economics teachers -- South Africa; Women in higher education -- South Africa